Natural Gas Reform Policies for the Development of Indonesian Chemical and Petrochemical Industries: Proposals and Recommendations - Soesilo, Triharyo I; Maskan, Fazi’et (ASEAN Journal of Chemical Engineering, 2022)
In industrialized nations, natural gas is not only used as an energy source but also as a raw material for the chemical and petrochemical industries. Indonesia, one of the largest producers of natural gas, uses only less than 8% of the gas produced for its chemical and petrochemical industries. By increasing the amount of gas used as feedstock for chemical and petrochemical industries, Indonesia will generate more income for the government and provide employment. To do this, however, current Indonesian government policy on natural gas production needs to be reformed. This paper outlines an across-the-board reform policy on natural gas with the objective of optimizing the natural gas usage of the chemical and petrochemical industries.